POKA YOKE TO PREVENT HUMAN ERROR AT MOULDING PROCESS OF INTEGRATED CIRCUIT ASSEMBLY - Arif Rahman Hakim; James Hellyward (SIGMA TEKNIKA, 2021)
This article describes a study conducted on the method to prevent error in manufacturing. Two cases in Integrated Circuit manufacturing was observed regarding human error occurred in moulding process. A technical solution was applied to prevent the case to occur. Mechanical approach solution named poka yoke was applied to the location of problem. It is proven that the solution is effective in preventing similar error to occur.